2019
DOI: 10.1364/boe.10.000817
|View full text |Cite
|
Sign up to set email alerts
|

Is it possible to measure hemodynamic changes in the prefrontal cortex through the frontal sinus using continuous wave DOT systems?

Abstract: The present work shows the capability of near infrared (NIR) light to reach the cerebral cortex through the frontal sinus using continuous-wave techniques (CW-DOT) in a dual study. On the one hand, changes in time during the tracking of a blood dye in the prefrontal cortex were monitored. On the other hand, hemodynamic changes induced by low frequency of transcranial magnetic stimulation applied on the prefrontal cortex were recorded. The results show how NIR light projected through the frontal sinus reaches t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Peak The results show that DOT detects the same areas as fMRI at a functional level. These results can be used to corroborate the reliability of Bayesian filtering applied on the frontal cortex through a cognitive task crossing barrier, such as the presence of frontal sinus where scalp-brain distance vary across the subject [13]. Additionally, cognitive signals generate more subtle relative activation changes, unlike motor or visual tasks.…”
Section: Anatomical Regionsupporting
confidence: 52%
See 2 more Smart Citations
“…Peak The results show that DOT detects the same areas as fMRI at a functional level. These results can be used to corroborate the reliability of Bayesian filtering applied on the frontal cortex through a cognitive task crossing barrier, such as the presence of frontal sinus where scalp-brain distance vary across the subject [13]. Additionally, cognitive signals generate more subtle relative activation changes, unlike motor or visual tasks.…”
Section: Anatomical Regionsupporting
confidence: 52%
“…The optical properties for each tissue layer in the human head were measured according to the distance between the source-detector pairs that were placed on the head surface. At a distance of around 3-4 cm between a source-detector pair, the photons contain information regarding the optical properties from both intracerebral and extracerebral layers, whereas, at a distance of 1-2 cm between the source-detector pair, the photons contain mostly information from extracerebral layers [13].…”
Section: Optical Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies have showed the reliability of Bayesian‐filtering on raw DOT data, one based on hemodynamic response measurement during a cognitive task [72], and another during repetitive transcranial magnetic stimulation [92]…”
Section: Filtering Methodsmentioning
confidence: 99%